Growth in girls with Turner syndrome - Isojima, Tsuyoshi; Yokoya, Susumu (Frontiers in Endocrinology, 2023)
Turner syndrome (TS) is a chromosomal disorder affecting females characterized by short stature and gonadal dysgenesis. Untreated girls with TS reportedly are approximately 20-cm shorter than normal girls within their respective populations. The growth patterns of girls with TS also differ from those of the general population. They are born a little smaller than the normal population possibly due to a mild developmental delay in the uterus. After birth, their growth velocity declines sharply until 2 years of age, then continues to decline gradually until the pubertal age of normal children and then drops drastically around the pubertal period of normal children because of the lack of a pubertal spurt. After puberty, their growth velocity increases a little because of the lack of epiphyseal closure. A secular trend in height growth has been observed in girls with TS so growth in excess of the secular trend should be used wherever available in evaluating the growth in these girls. Growth hormone (GH) has been used to accelerate growth and is known to increase adult height. Estrogen replacement treatment is also necessary for most girls with TS because of hypergonadotropic hypogonadism. Therefore, both GH therapy and estrogen replacement treatment are essential in girls with TS. An optimal treatment should be determined considering both GH treatment and age-appropriate induction of puberty. In this review, we discuss the growth in girls with TS, including overall growth, pubertal growth, the secular trend, growth-promoting treatment, and sex hormone replacement treatment.